Higher Body-Mass Index and Lower Gray Matter Volumes in First Episode of Psychosis - Kolenič, Marián; Španiel, Filip; Hlinka, Jaroslav; Matějka, Martin; Knytl, Pavel; Šebela, Antonín; Renka, Jiří; Hajek, Tomas (Frontiers in Psychiatry, 2020)
Background: Neurostructural alterations are often reported in first episode of psychosis (FEP), but there is heterogeneity in the direction and location of findings between individual studies. The reasons for this heterogeneity remain unknown. Obesity is disproportionately frequent already early in the course of psychosis and is associated with smaller brain volumes. Thus, we hypothesized that obesity may contribute to brain changes in FEP. Method: We analyzed MRI scans from 120 patients with FEP and 114 controls. In primary analyses, we performed voxel-based morphometry (VBM) with small volume corrections to regions associated with FEP or obesity in previous meta-analyses. In secondary analyses, we performed whole-brain VBM analyses. Results: In primary analyses, we found association between FEP and lower GM volume in a) left fronto-temporal region (pTFCE=0.008) and b) left postcentral gyrus (pTFCE=0.043). BMI was associated with lower GM volume in left cerebellum (pTFCE<0.001). In secondary analyses, we found association between FEP and lower GM in the a) cerebellum (pTFCE=0.004), b) left frontal (pTFCE=0.024) and c) right temporal cortex (pTFCE=0.031). BMI was associated with lower GM volume in cerebellum (pTFCE=0.004). Levels of C-reactive protein, HDL and LDL-cholesterol correlated with obesity related neurostructural alterations. Conclusions: This study suggests that higher BMI, which is frequent in FEP, may contribute to cerebellar alterations in schizophrenia, possibly through low-grade systemic inflammation. As previous studies showed that obesity-related brain alterations may be reversible, our ﬁndings raise the possibility that improving the screening for and treatment of obesity and associated metabolic changes could preserve brain structure in FEP.